Tourist risk assessment of pollen allergy in tourism attractions: A case study in the Summer Palace, Beijing, China - Zhou, Yu; Dai, Junhu; Liu, Haolong; Liu, Xian (Frontiers in Public Health, 2022)
Pollen allergy has already been an increasingly prominent ecosystem disservice in tourism attractions. However, few studies have assessed the tourist risk of pollen allergy through integrating multidisciplinary knowledge of ecology, medicine, phenology, and risk management. Basing on the conceptual framework of risk assessment proposed by UNISDR, we first established an index system of pollen-allergy risk for tourists in attractions and outlined assessment methods.18 available indexes were put forward to cover three aspects: hazard of plant allergen, tourist vulnerability, and resilience of assessment units. Subsequently, taking the Summer Palace as the case study area, we conducted a tourist risk assessment of pollen allergy. Values of nine available indexes were obtained via ecological investigation, phenological observation, and data mining of visitors’ logs on Sina Weibo. Risk levels of spring pollen allergy for tourists in different assessment units were revealed by combining the green zone allergenicity index model and three-dimensional risk assessment matrix. The results showed that: (1) There were 7 primary pollen-allergenic plants in the Summer Palace, including Platycladus orientalis, Sabina chinensis, Salix babylonica, Pinus tabulaeformis, Populus tomentosa Carr, Morus alba L. and Fraxinus chinesis, among which Platycladus orientalis and Salix babylonica were the highest allergenic. (2) Among 18 spots, tourists faced the highest risk level of pollen allergy in spring at 3 spots, namely the Hall of Serenity, Hall of Benevolence and Longevity, and Gallery of Literary and Prosperity. (3) The two routes of the Long Corridor and Longevity Hill scored high on the risk level. (4) Among 4 areas, risk levels of the Front-hill and Rear-hill areas were high. Given the increasing spatial-temporal uncertainty of pollen allergy and tourist behaviors under global warming and urbanization, the related monitoring should be strengthened in the future. Furthermore, the dynamic and improved assessment of pollen-allergy risk should be institutionalized and be integrated into the evaluation of tourism experience quality. Tourism administration should make full use of relevant assessment results and conduct more effective risk communication.